Convergências teóricas entre Veblen e Keynes - Corradi, Lígia Lóss (2016)
This research aims to discuss the convergence and divergence issues between the economic theories of Thorstein Bunde Veblen and John Maynard Keynes. To meet these objectives, it presents firstly, the core principals of Veblen’s theoretical underpinnings (based on his selected pieces), such as: instincts, habits, and institutions that shape human behavior. According to the author, the evolution of these elements is important to the understanding of the structure and the functioning of the current capitalist system. After that, the dissertation examines the Keynesian thought (developed after his General Theory, 1936) about the effective demand, the role of long-term expectations to determining employment levels and income, the economic cycles, and his perspective on the future of the capitalist system. The research found similarities in the views of both authors about the components of aggregate demand, about the determination of employment and income, the use of social conventions in decision-making agents, and the economic cycle. Nevertheless, the opinion of the authors on the future of capitalism is divergent.